1979
DOI: 10.1001/jama.1979.03290430029018
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis and Pregnancy

Abstract: When severe renal failure requiring hemodialysis complicates pregnancy, there is hesitation to continue the pregnancy. However, successful hemodialysis in pregnancy is being reported with growing frequency. Fetal survival and even conception is possible in patients undergoing dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The levels of these hormones in pregnancy of patients with CRF and secondary hyperparathyroidism have yet to be determined. Fertility is impaired in women with CRF and the small numbers of successful pregnancies in dialysis patients are frequently associated with complications and perinatal loss [15][16][17][18][19]. In a pregnant patient on chronic haemodialysis we observed that the serum immunoreactive PTH (iPTH) level decreased without any intervention, from over 1250 pg\ml before pregnancy to 200 pg\ml during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of these hormones in pregnancy of patients with CRF and secondary hyperparathyroidism have yet to be determined. Fertility is impaired in women with CRF and the small numbers of successful pregnancies in dialysis patients are frequently associated with complications and perinatal loss [15][16][17][18][19]. In a pregnant patient on chronic haemodialysis we observed that the serum immunoreactive PTH (iPTH) level decreased without any intervention, from over 1250 pg\ml before pregnancy to 200 pg\ml during pregnancy.…”
Section: Introductionmentioning
confidence: 99%